PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IV SD - ayu anggraeni; Henry Suryo Bintoro; Jayanti Putri Purwaningrum (Journal Prakarsa Paedagogia, 2020)
The reasearch aim to measure improvement in the understanding concept mathematics abilities after using the Discovery Learning Model. The understanding concept mathematics abilities is one of the important goals in learning, providing an understanding that the material taught to students is not just memorization, but more than that with understanding students can better understand the concept of the subject matter itself. In this study, researchers will use the Discovery Learning model which is one of the learning models that requires students to find and find their knowledge in accordance with their own abilities, so that students' ability to understand concepts can be improved. The results of this research showed there is an increase in students' understanding of mathematical concepts.